Environmental Concerns in the Framework of General Sustainable Development and Tourism Sustainability - PURWANDA, Eka; ACHMAD, Willya (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022, 2022)
The goal of this study is to provide a synthesis and update tour on general sustainable development and tourism sustainability taking into consideration also the environmental concerns. In this paper, we show how environmental concerns, which were once thought to be the most important aspect of sustainable development, are still one of the most important factors to consider when attempting to ensure sustainable growth while taking both economic and social considerations into account worries. This study emphasizes the importance of the local region in our days, in addition to the importance of the global region, as well as the need for sustainability to be integrated with social responsibility activities. Furthermore, this study demonstrates how sustainable development may be "traced" back to statements, meetings, and documents held around the world and in each country. All of this demonstrates the importance of sustainable development, as well as the significant worry it raises in regard with environmental concerns. The second part of this article discusses the evolution of sustainability in the tourism business. Particular attention is placed on how the sector might be related to overall sustainable development.